Education of Children in Different according to the Structure Families - Tetyana Dovzhenko (Pedagogical Discourse, 2012)
The peculiarities of education of one child in a family, positive and negative characteristics of education in large family are revealed in the article. Typical difficulties of education of a child in one-parent family are also selected. The principles of family education are described: dialogue in communication; acceptance of a child; independences of a child.